Culture of common carp (Cyprinus carpio) with defined flesh quality for prevention of cardiovascular diseases using finishing feeding strategy - Mraz, Jan; Zajic, Tomas; Pickova, Jana (Neuro endocrinology letters, 2012)
OBJECTIVES: Fish is the major source of n-3 polyunsaturated fatty acids (n-3 PUFA) which are well known to have positive effects in prevention of cardiovascular diseases. This study investigated the possibility to produce common carp with defined flesh quality using finishing feeding strategy and predict changes of fillet FA by a dilution model. METHODS: During the 110-day experiment, fish were fed diets with two different vegetable oils (rapeseed/linseed blend, VO; olive oil, OO) only, or with a subsequent fish oil (FO) finishing treatment for 30 or 60 days. Fillet FA composition was measured and data were compared to the ones predicted by the dilution model. RESULTS: The FO finishing treatment resulted in the higher percentage of SFA (from 19.1% to 23.6%; p<0.001), MUFA (from 46.8% to 51.9%; p<0.001), n-3 PUFA (from 3.6% to 7.4%; p<0.001) and lower n-6 PUFA (from 30.5% to 16.9%; p<0.001) and n-6/n-3 ratio (from 8.7 to 2.3; p<0.001) in groups previously fed the VO diet and in lower MUFA percentage (from 67% to 63%; p<0.001) and n-6/n-3 ratio (from 8.2 to 2.8; p<0.001) and higher n-3 PUFA percentage (from 1.5% to 4.5%; p<0.001) in group previously fed the OO diet. The dilution model gave a good prediction for fillet FA changes (slope of the regression line 0.97-1.00; R2 value of 0.992-0.996). CONCLUSION: The finishing feeding strategy is suggested for production of common carp with a required flesh FA composition for purposes of special nutritional needs, especially for primary and secondary prevention of cardiovascular disease.
Keywords: Animals; kosterní svaly; Fatty Acids, Omega-6; Fatty Acids, Omega-3; Female; ženské pohlaví; kyseliny dokosahexaenové; Animal Feed; kapři; Fish Oils; kyselina eikosapentaenová; lidé; vodní hospodářství; Eicosapentaenoic Acid; Muscle, Skeletal; Aquaculture; omega-3 mastné kyseliny; Male; Cardiovascular Diseases; Carps; krmivo pro zvířata; kardiovaskulární nemoci; kyseliny mastné omega-6; zvířata; mužské pohlaví; rybí oleje; Docosahexaenoic Acids; Humans